If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3c + 1 = -5 Reorder the terms: 1 + -3c = -5 Solving 1 + -3c = -5 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3c = -5 + -1 Combine like terms: 1 + -1 = 0 0 + -3c = -5 + -1 -3c = -5 + -1 Combine like terms: -5 + -1 = -6 -3c = -6 Divide each side by '-3'. c = 2 Simplifying c = 2
| -7(1-y)=3(y-1) | | N-4+1=3(n-1) | | 2h-4=-44-3h | | 2x^2+10=20 | | 5u+4u=45 | | 7+3x=5+4x | | 3(x+2)=2x+11 | | 4(x+1.12)=3x | | 2k+5(k-2)=4 | | 2d-3(d-4)=2 | | 4(2x-8)=0 | | 4(x+2)-2=3+2x+2(x+3) | | (n+2)*6=66 | | 3x-4(x+3)=9 | | 5x+9=3x-7 | | 3x+4(x+3)=9 | | 7a+6=55 | | 8d^2-10d-3=0 | | -8(x+5)-(9x+7)=4 | | x*12-148=x*5-8 | | 3(2x+5)=25+x | | 4T+3=T+12 | | 18s^2-39s+20=0 | | 9n-28=62 | | x^2-13x+20=-3x-1 | | 90-6x=12x+20 | | 2x-5yi=16+25i | | 2b^2+19b+42=0 | | 5x+150=14x-12 | | 14-8x=34-22x | | 5+4x=11+2x | | 14-8x=34-22 |